Gratitude and Resilience among Students with Disabilities in Indonesia - Lessy, Putri Pratiwi; Huwae, Arthur (Indonesian Journal of Disability Studies, 2024)
Students with disabilities face challenges in their daily lives due to their limitations. This often causes them a lot of stress, as they have to adapt to an environment dominated by non-disabled students. To deal with this difficult situation and maintain their survival, students with disabilities need to have abilities that can support them, namely resilience. The purpose of this study is to determine the relationship between gratitude and resilience in students with disabilities. This study used a quantitative method with a correlation design. The sample of this study consisted of 108 students with disabilities obtained by purposive sampling technique. Measurements were made using the Indonesian Gratitude Scale (Skala Bersyukur Indonesia (SBI)) (a=0.88) and The Connor-Davidson Resilience scale (CD-RISC) (a=0.92). Data analysis used Karl Pearson's Product Moment method, and found a correlation coefficient between gratitude and resilience of 0.316 with a significance of 0.000 (p<0.01). The results showed a significant positive relationship between gratitude and resilience in students with disabilities. This shows that gratitude is a factor that plays a role in increasing the resilience of students with disabilities. The implication of this study is the importance of students with disabilities having gratitude that can help them adapt and thrive in difficult situations. It is hoped that future research can use different variables or different subjects to broaden understanding in this field.Top of Form